HYGIENE DAN SANITASI PENGOLAHAN MAKANAN KELUARGA ANGGOTA LEMBAGA PEMBERDAYAAN KESEJAHTERAAN KELUARGA (LPKK) - Tri Hermawan (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
This study aimed to know the description of hygiene and sanitation of family foodmanagement among the members of familywelfare empowerment organization. Data collection methods used questionnaires and documentation. Data analysis method used descriptive analysis to descriptive the score of mean,median, mode, and standard deviation. Thisstudy shows that hygiene and sanitation of family food management among the members offamily welfare empowerment organization wasin enough category with the frequency 47.44%.The hygiene and sanitation of family food management among the members of family welfareempowerment organization could be seen fromindicators of choosing the food ingredients,managing foods, and servicing foods. a) Theindicator of choosing the food ingredients wasin enough category with the frequency 47.44%.b) The indicator of managing foods was inenough category with the frequency 48.72%. c)The indicator of servicing foods was in enoughcategory with the frequency 62.82%. Thus, theindicator of servicing foods was more dominantdetermining hygiene and sanitation of familyfood management among the members of family welfare empowerment organization